The Drug Enforcement Administration - Stefoff, Rebecca (New York : Chelsea, 1989)
Surveys the history, structure, and current functions of the Drug Enforcement Administration and describes its influence on modern society.
Includes bibliographical references.
Keywords: U.S. -- Drug Enforcement Administration; Narcotics -- Control